Ecological-biomorphological structure of roadside vegetation along the highways of Minsk and the Minsk Region - Shavalda, Yauheni S.; Sudnik, Aliaksandr V. (Experimental Biology and Biotechnology, 2024)
An assessment was made of the ecological (depending on the trophicity (edaphotope) and moisture (hydrotope) of the soil) and biomorphological (according to the Raunkiaer and Serebryakov classification systems of life forms) structure of vegetation within various exposures of the right-of-way along the highways of Minsk and the Minsk Region. A total of 267 plant species have been identified, including 7 species of bryophytes and 37 species of trees and shrubs. The edaphotopic structure is dominated by mesotrophs (96 species, or 36.9 %) with a shift towards eutrophicity (mesoeutrophs (85 species, or 32.7 %) and eutrophs (54 species, or 20.8 %) are widely represented). The hydrotopic structure is characterised by the dominance of mesophytes (160 species, or 61.5 %) with signs of xerophytisation of the flora (there are 55 species, or 21.2 % xeromesophytes). According to the Raunkiaer system, hemicryptophytes (139 species, or 53.5 %) and therophytes (64 species, or 24.6 %) dominate (the hemicryptophytic-therophytic type of flora). According to the Serebryakov system is dominated by taproot (87 species, or 39.5 %), long-rhizome (44 species, or 20.0 %) and short-rhizome (40 species, or 18.2 %) forms. The features of floristic diversity and ecological-biomorphological structure of roadside vegetation were established depending on the design of the right-of-way and the preservation of the soil cover under various anthropogenic impacts. Brief recommendations are given for caring for the right-of-way in conditions of an abundance of therophytes and taproot forms of plants.
Keywords: highway; right-of-way; roadside vegetation; edaphotopic structure; hydrotopic structure; biomorphological structure according to Raunkiaer; biomorphological structu re according to Serebryakov